LEGISLATION AND THE ADMINISTRATION OF TAXATION OF CO-OPERATIVE SOCIETIES: DRAWING AN INTERSECTION FOR SUSTAINABLE DEVELOPMENT - Akanji, Ajibola Anthony (International Journal of Cooperative Law, 2025)
Nigerian co-operatives are enabled by both national and subnational legislation. Section 20 (1) and (2) Nigerian Co-operative Societies Act, (NCSA)CAP. N98, exempts societies from the payment of stamp duties chargeable under the Stamp Duties Act CAP. S8. Section 23 (1) (b)of theCompanies Income Tax Act, CAP. C21and Section 26 (1) (c)of the Capital Gains Act, CAP. C1exempts societies from taxation of profits and gains. Current statistics show that co-operatives are more likely to possess characteristics of community organizations than commercial enterprises, with the consequence that their potential is sub-optimally utilized. There is a need for an appraisal of the specified circumstances in conjunction with some elements of their enabling legislation. The exemption from taxation is identified as a drawback in the implementation of the sustainable development agenda. This points to the need to integrate elements of company law into co-operative legislation to remedy the identified deficiencies.